APPLICATION OF KINETIC RECOVERY PROGRAMS IN PERFORMANCE SPORTS DANCE PATHOLOGIES - SOPA, Ioan Sabin; HRIȚCU-MEȘENSCHI, Dennis; NEAGU, Nicolae; SZABO, Dan Alexandru (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
For the detection of the flat foot and ligament laxity, the method of visual observation of the anatomical landmarks, the planogram on paper and the test of bearing body weight were used. At the same time, to test the stability of the ankle joint, we used the unipodal test on Bosu ball, where it was measured in seconds how much the subjects managed to maintain the unipodal position on Bosu ball. For the detection of low back pain, the method of individual interviewing of each athlete, the VAS scale of pain, the DLLT test (Double Leg Lowering Test) and the visual evaluation of any malalignments present in the bone structures was used. Applying the protocol for flat foot pathology, we obtained an improvement of the plantar arch in all subjects, as evidenced by the improvement of paper planograms where the decrease of the plantar footprint on the medial part of the foot was observed in all subjects of the experiment group. Compared to the standard protocol applied to the control group, we obtained by applying our protocol an improvement of the Achilles tendon line in orthostatic in 9 out of 10 subjects, while when applying the standard protocol, only 7 out of 10 subjects were observed. In conclusion, applying the kinetic protocol to recover post-training low back pain has improved low back pain, proving to be more beneficial than the standardized protocol for dancers, especially for female subjects. Article history: Received 2022 August 07; Revised 2022 September 27; Accepted 2022 September 28; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. Aplicarea protocolului kinetic de recuperare în patologiile dansului sportiv de performanță. Pentru depistarea laxității piciorului plat și a ligamentelor s-au folosit metoda de observare vizuală a reperelor anatomice, plantograma pe hârtie și testul de susținere a greutății corporale. Totodată, pentru a testa stabilitatea articulației gleznei, am folosit testul unipodal pe mingea Bosu, unde s-a măsurat în secunde cât de mult au reușit subiecții să mențină poziția unipodală aceasta. Pentru a detecta durerile de spate au fost utilizate metoda de intervievare individuală a fiecărui atlet, scala de durere VAS, testul DLLT (Testul dublu de coborâre a picioarelor) și evaluarea vizuală a oricăror malalinieri prezente în structurile osoase. Aplicând protocolul pe care l-am creat pentru patologia piciorului plat, am obținut o îmbunătățire a arcului plantar la toți subiecții, dovadă fiind îmbunătățirea plantogramelor de hârtie unde s-a observat o scădere a impresiei plantare pe partea medială a piciorului la toți subiecții grupului experimental. În comparație cu protocolul standard aplicat grupului de control, am obținut prin aplicarea protocolului nostru o îmbunătățire a liniei tendonului lui Ahile în ortostatism la 9 din 10 subiecți, în timp ce aplicarea protocolului standard a fost observată la doar 7 din 10 subiecți. În concluzie, aplicarea protocolului kinetic de recuperare a lombalgiei post-exercițiu a adus un rezultat pozitiv în ceea ce privește ameliorarea lombalgiei, dovedindu-se a fi mai benefică decât protocolul standardizat pentru dansatori, în special pentru subiecții de sex feminin. Cuvinte cheie: recuperarea kinetică, sportul de performanță, patologiile dansatorilor, traumatologia sportivă.